2019
DOI: 10.1177/0192513x19832938
|View full text |Cite
|
Sign up to set email alerts
|

Interactional Synchrony and Child Gender Differences in Dyadic and Triadic Family Interactions

Abstract: Based on family systems theory, our objectives were to examine the association between dyadic parent–child interactional synchrony (mother–child and father–child) and triadic mother–father–child interactional synchrony and the effect of the child’s gender on the family interactional synchrony at the child’s third year. Forty-three low-income Brazilian families (mother, father, and child) were observed in free play interaction. Multidimension assessments of the degree of dyadic and triadic interactional synchro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 43 publications
1
10
1
Order By: Relevance
“…The fact that paternal relatedness SG was associated with triadic family synchrony may suggest that, in our sample of Brazilian low-income parents, fathers' traditional orientation towards dependency is especially influential in family interactive patterns. The empirical evidence provided in the present study supporting that fathers' more traditional SGs have an impact on triadic interactive patterns added to our previous finding that fathers may have a greater influence in the triadic family interaction patterns, in comparison to mothers (De Mendonça et al, 2019) calls for the debate about the type of maternal and paternal influences that Brazilian low-income children may suffer and the consequences of such influences for their future values and behaviors. It may be that children from a low-income population in Brazil are being exposed mainly to fathers' values and practices, when the family plays together and, thus, to a parenting style characterized by the encouragement of the child's dependency and adherence to more traditional values and norms.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…The fact that paternal relatedness SG was associated with triadic family synchrony may suggest that, in our sample of Brazilian low-income parents, fathers' traditional orientation towards dependency is especially influential in family interactive patterns. The empirical evidence provided in the present study supporting that fathers' more traditional SGs have an impact on triadic interactive patterns added to our previous finding that fathers may have a greater influence in the triadic family interaction patterns, in comparison to mothers (De Mendonça et al, 2019) calls for the debate about the type of maternal and paternal influences that Brazilian low-income children may suffer and the consequences of such influences for their future values and behaviors. It may be that children from a low-income population in Brazil are being exposed mainly to fathers' values and practices, when the family plays together and, thus, to a parenting style characterized by the encouragement of the child's dependency and adherence to more traditional values and norms.…”
Section: Discussionsupporting
confidence: 76%
“…With the objective to fill these gaps, we have two specific goals: (1) to compare maternal and paternal cultural orientation in their SGs and FAM; (2) to examine the associations between maternal and paternal SGs and FAM and family triadic play interaction. Considering that parental behavior, especially fathers' behavior, is highly influenced by their respective social roles within society (De Mendonça et al, 2011;De Mendonça et al, 2019), we will observe family triadic interactions to gain a deeper understanding of family system dynamics in relation to culturally expected maternal and paternal roles. The triadic interaction provides a context in which multiple forms of interaction can be observed, as opposed to the dyadic interaction that offers less interactional possibilities.…”
Section: Socialization Goals Of Brazilian Mothers and Fathersmentioning
confidence: 99%
“…The available behavioral data suggest that fathers’ and mothers’ interactional behavior toward their children should in principle not substantially differ. For example, father– and mother–child dyads appear to show similar levels of interpersonal behavioral synchrony during their interactions (de Mendonça, Bussab, & Kärtner, 2019 ; Feldman, 2003 ), and father– and mother–child interaction quality seems to be comparable more generally (e.g., Piskernik & Ruiz, 2020 ). These results suggest that father–child dyads might show comparable associations of INS to state‐like factors, such as behavioral reciprocity, as mother–child dyads.…”
mentioning
confidence: 99%
“…While Nguyen et al ( 2020a ) observed that child agency, a state‐like factor, could facilitate INS within mother–child dyads, Quiñones‐Camacho et al ( 2019 ) emphasize the role of child irritability during recovery phases of stressful interactions as potentially inhibiting task‐related INS. Moreover, the biological sex of the child seems to be related to the interaction qualities of father–child dyads (de Mendonça et al, 2019 ). Crucially, however, the evidence here is somewhat inconsistent.…”
mentioning
confidence: 99%
“…Furthermore, both mothers and fathers of children should be recruited in future studies and parental demographic characteristics should be recorded to compare respective levels of neurophysiological coherence with their children and explore potential association with personal attributes. Gender-based differences in childparent dyadic interactional synchrony have been previously noted (De Mendonça et al, 2019).…”
Section: Limitationsmentioning
confidence: 81%